Deprivation, Frustration and Aggression: An interrogation of Fulani Herdsmen Terror in Nigeria - Olu-Adeyemi, Lanre (Advances in Social Sciences Research Journal, 2017)
Abstract The Fulani Herdsmen has been ranked as the fourth deadliest terrorist group in the world by the 2014 Global terrorism Index. This paper examines the activities of the Fulani Herdsmen against the background of their persistent violent attacks on farms, farmers and communities across Nigeria to the detriment of national unity and security. Relying on the theory of Deprivation, Frustration and Aggression; the paper relies on the strength of secondary (including historical) and to some extent, primary sources of data to situate the Fulani Herdsmen Terror as the nexus of the deprivations emanating from the plethora of social, economic, environmental and political situations in Nigeria. The paper makes recommendations on ways to bring the terror attacks under control. Keywords: Fulani Herdsmen, Terrorism, National Unity.